2009
DOI: 10.1007/s00264-009-0747-8
|View full text |Cite
|
Sign up to set email alerts
|

Human cartilage glycoprotein 39—biomarker of joint damage in knee osteoarthritis

Abstract: Human glycoprotein of cartilage (YKL-40) synthesizes chondrocytes and synovial cells in inflammatory conditions or remodels the outer cell matrix in osteoarthritis. The aim of this study was to conduct a parallel analysis between thickness of cartilage and length of osteophytes, ultrasound indicators of joint destruction, with levels of YKL-40 in serum in patients with primary osteoarthritis. Ultrasound findings and concentration of YKL-40(ng/ml) were examined in 88 patients. The average value cartilage thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Within OA joints, YKL-40 is secreted into the synovial fluid by chondrocytes, activated macrophages and synovial fibroblasts [16,31]. Different investigations have demonstrated that osteoblasts and osteocytes present in osteophytes expressed YKL-40 [14,18]. Thus, our finding of higher YKL-40 levels in synovial fluid reflects OA changes in the joint tissue.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Within OA joints, YKL-40 is secreted into the synovial fluid by chondrocytes, activated macrophages and synovial fibroblasts [16,31]. Different investigations have demonstrated that osteoblasts and osteocytes present in osteophytes expressed YKL-40 [14,18]. Thus, our finding of higher YKL-40 levels in synovial fluid reflects OA changes in the joint tissue.…”
Section: Discussionsupporting
confidence: 58%
“…Most published studies used radiographic examination to assess the disease process in joints. The data available are quite controversial [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Tenascin and fibronectin are further molecules which modulate the interactions between chondrocytes and the surrounding microenvironment [47]. Cartilage oligomeric matrix protein (COMP) and other non collagenous proteins are markers of cartilage turnover and degeneration and are upregulated following proinflammatory stimuli [48][49][50].…”
Section: Main Features Of Articular Cartilagementioning
confidence: 99%
“…CHI3L1 was found to be a major secreted protein of human articular cartilage chondrocytes and synovial cells [6,7]. In addition, CHI3L1 has been detected in sera of patients with various diseases including inflammatory bowel disease, pulmonary sarcoidosis, systemic sclerosis, and liver fibrosis [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%